Relations of the level of morphological differentiation and metabolic activity of squamous carcinomas of oropharyngeal areas according to positron emission tomography - M. Tisch; A.V. Lysak; O. O. Diadyk (Zaporozhye State Medical University, 2019)
Today verification and grading of oropharyngeal tumors, determination of their malignant potential remain an actual problem both in diagnostics and in predicting the growth of tumors. The aim of the study was to determine the metabolic activity of the oropharyngeal tumors due to positron emission tomographic diagnosis and comparison with the morphological (histological) pattern. Materials and methods. From May 1, 2012 to January 1, 2015, on the basis of the military hospital of Bundeswehr in Ulm, we investigated 121 cases of squamous-cell carcinoma of the oropharyngeal area with preoperative use of positron emission tomographic (PET) diagnostics. We have studied the relationship between the accumulation of 2-fluoro [18F] -2-deoxy-D-glucose and certain morphological criteria. The study assessed the level of differentiation according to the method of Anneroth et al., 1987 and Bryne et al., 1992. Results. After selecting and viewing the biopsy and surgical material, depending on the level of morphological differentiation of the tumors, the patients were divided into three main groups. In the first, which includes highly differentiated - G1 tumors - 22 patients, in group 2, in contrast to G2 - 45 and in group 3, poorly differentiated G3 - 54. We have morphologically described all these groups. Later in the groups, PET results were evaluated according to the SUVmax index. Comparing the indices, a statistically significant difference was found between the groups (P < 0.001 by the Kruskal-Wallis criterion for all indicators). So, as the level of Me decreases, the differentiation of SUVmax tumors significantly (P < 0.05) increases, and the growth of SUVmax indicates an increase in the degree of malignancy of the tumors. Conclusions. On the basis of the conducted research, a statistically visible relationship between the SUVmax and the level of morphological differentiation of squamous carcinomas of the oropharyngeal area was established. The possibility of using the method of PET diagnostics as a possible criterion for assessing the level of differentiation of tumors, including complex squamous carcinomas of the oropharyngeal area, has been demonstrated.